2018
DOI: 10.1155/2018/9081742
|View full text |Cite
|
Sign up to set email alerts
|

Small Bowel Obstruction with Perforation Secondary to PillCam

Abstract: We present a case of a 63-year-old female who presented with small bowel obstruction and perforation secondary to a retained PillCam®. She initially presented with iron-deficiency anaemia (haemoglobin 44 g/L, ferritin 190 mcg/L). After unremarkable upper and lower gastrointestinal endoscopies and biopsies, she was referred for wireless capsule endoscopy (WCE). Four days afterwards she re-presented with small bowel obstruction and perforation related to the PillCam, which was confirmed on X-ray, on computed top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…An examination in which visualizing the first cecal image is not possible during the recording time is known as incomplete examination, although this does not necessarily imply retention 18 . The factors associated with incomplete examination include: prolonged gastric transit time, gastroparesis, diabetes mellitus, poor intestinal preparation, hyperthyroidism, prior intestinal surgery, hospitalized patients, and especially those who are bedridden and in the intensive care unit 11,14 . A study carried out by Stanich et al 14 showed the relationship between increased physical activity and shorter intestinal transit time, but no association is demonstrated with a decrease in cases of incomplete examinations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An examination in which visualizing the first cecal image is not possible during the recording time is known as incomplete examination, although this does not necessarily imply retention 18 . The factors associated with incomplete examination include: prolonged gastric transit time, gastroparesis, diabetes mellitus, poor intestinal preparation, hyperthyroidism, prior intestinal surgery, hospitalized patients, and especially those who are bedridden and in the intensive care unit 11,14 . A study carried out by Stanich et al 14 showed the relationship between increased physical activity and shorter intestinal transit time, but no association is demonstrated with a decrease in cases of incomplete examinations.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that IBD can be considered a risk factor for CR, as prior small bowel resection, abdominal radiation therapy and nonsteroidal anti-inflammatory drugs chronic use also are, which reinforces the importance of a good anamnesis of the patient who is to undergo treatment with VCE 4,5.7 . Other contraindications include obstructive symptoms, an ileocolonoscopy showing stenosis, radiological evidence, or suspicion of stenosis of the GI tract and follow-up of small bowel tumors [11][12][13] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 A la fecha, existen muy pocos casos reportados de perforación intestinal debido a retención de CE, la mayoría de ellos ocurren en pacientes con enfermedad de Crohn, [6][7][8] el íleon terminal es el sitio de perforación más frecuente, solamente un caso ocurrió en el yeyuno distal. 9 Otras etiologías que pueden ocasionar retención de cápsula y perforación incluyen neoplasias [6][7][8] y adherencias secundarias a cirugía abdominal. 10 A la fecha, no ha sido reportado ningún caso de perforación de intestino delgado secundario por CE, en un paciente con enteritis por radiación (ER).…”
Section: Introductionunclassified